Intersubjektivitas dan Gaya Kamera dalam Film Etnografi - Aryo Danusiri (Antropologi Indonesia, 2018)
This article is about the use of observational camera style in articulating intersubjectivity. The case is my experience in making Lukas' Moment (2005), an ethnographic film shot in Merauke, Papua. The film is about Papuans’ intersubjectivity toward indigeneity in the post-2000 riot Papua. I observed the experiences of three Papuan entrepreneurs in processes of building their enterprises which in different ways involve politics of indigeneity. Following the existential-phenomenological anthropology approach, I explicate intersubjectivity as instable formation of subjects engaging in their process of being-in-the-world. In the filming process, I experienced two modalities of observational camera, which I called hunting and fishing modes of visuality. The hunting mode focuses on searching for preconceived images of targeted social scenes to satisfy a research goal, while the fishing mode is about building correspondence with the rhythm of the subject’s social processes in everyday life in order to capture the unexpected social scenes. As it is characterized by establishing cinematic correspondence with the subject’s path of life, I argue that the fishing mode is more suitable as an ethnographic endeavor which aims to broaden the horizon of humanity instead of predicting it.